Implementasi Sistem Penjaminan Mutu Internal (SPMI) dalam Meningkatkan Mutu Pendidikan di Sekolah - Sherwina Ranisa; Ahmad Suriansyah; Ratna Purwanti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the implementation of the Internal Quality Assurance System (SPMI) in improving the quality of education at SMAN 1 Jejangkit. A qualitative descriptive approach was used, with data collected through interviews, observations, and documentation. The results show that SPMI is implemented through five key cycles: setting standards, implementation, evaluation, control, and improvement. Strong school leadership, active participation from all school members, and the development of a quality culture support its success. Despite challenges such as limited resources and adapting to policy and technological changes, SPMI has had a positive impact on teaching quality, teacher competence, and compliance with national education standards. The study recommends enhancing digital integration and developing innovative, future-oriented curricula.